#TITLE_ALTERNATIVE# - CITA CAHYANI (NIM : 12212033), INDAH
The efficiency of LPG to miscibly displace oil from reservoir is very well written in literature. Althought LPG is well in displacement efficiency, but the cost of LPG make this method difficult to be applied in many oil fields. On the other hand, CO2 is relatively cheap depending upon the availability, but it is miscible with most crude oils only at high pressure and low temperature. CO2 requires still higher pressure to be miscible with heavy crude oils. Purposes of this study are determining the value of minimum miscibility pressure (MMP) of oil and gas (CO2-LPG) by using simulator, knowing the most effective WAG injection mechanism on field X, and getting information about mol fraction ratio of CO2 gas and LPG in order to maximize oil recovery on field X. Several scenarios of CO2 and LPG mixture are created to understand the effect of the ratio to the value of MMP and oil recovery. CMG-WINPROPTM simulator is being used to know the value of MMP. CMG-GEMTM is being used to know the value of the oil recovery. From the results of the simulations, LPG addition can lower the value of MMP. Water injection, as first injection in WAG method, gives better results because it can prevent early water breakthrough and prevent decline of reservoir pressure. LPG addition can improve oil recovery factor in WAG-CO2 method. The biggest oil recovery is achieved at 44.41% with 65 : 35 ratio of CO2 and LPG.